PENGARUH PERAN FARMASIS TERHADAP PENGETAHUAN PASIEN TENTANG PENATALAKSANAAN PENYAKIT DIARE DI PUSKESMAS RAWAT INAP SUKARAJA KOTA BANDAR LAMPUNG - Nopiyansyah Nopiyansyah; Yuli Wahyu Tri Mulyani; Tanzilla Evitasari; Riko Herdiansah (Program Studi Farmasi Universitas Tulang Bawang, 2022)
Diarrheal disease in developing countries like Indonesia is still a public health problem that can cause child death in the world. Diarrhea is a condition characterized by a person having loose stools three or more times a day. This case of diarrhea needs the role of pharmacists such as education to increase patient knowledge about the management of diarrheal diseases. Education is an activity to increase individual health knowledge regarding the management of risk factors for disease and healthy living behavior in an effort to improve public health status, prevent recurrence of disease and recover from disease. Factors that influence a knowledge that is age, education, occupation and sources of information. This study aims to determine whether there is a relationship between education and the level of patient knowledge about the management of diarrheal diseases at the Sukaraja Inpatient Health Center, Bandar Lampung City. This research is a non-experimental research with an observational analytic research design, using a one group pre-test and post-test study design that can be analyzed using the Statistical Product and Service Solutions (SPSS) method. This study was conducted for 2 months with the results of the study showing the characteristics of patients based on age, the most were 26-45 years old with 19 people (47.5%), high school education as many as 20 people (50%), and the most type of work was housewives 17 people (42.5%). The level of patient knowledge after being given an education can be seen from the Wilcoxon test with a significant value <0.005, stating that there is a relationship between education and the level of patient knowledge about the management of diarrheal diseases at the Sukaraja Inpatient Health Center, Bandar Lampung. Keywords: Diarrhea, Education, Knowledge Level.